Effects of Fosinopril and Pravastatin on Cardiovascular Events in Subjects With Microalbuminuria - Asselbergs, Folkert W.; Diercks, Gilles F.H.; Hillege, Hans L.; van Boven, Ad J.; Janssen, Wilbert M.T.; Voors, Adriaan A.; de Zeeuw, Dick; de Jong, Paul E.; van Veldhuisen, Dirk J.; van Gilst, Wiek H. (Circulation (New York, N.Y.), 2004)
Background— Microalbuminuria is associated with increased risk of cardiovascular events. We assessed whether therapeutic intervention aimed at lowering urinary albumin excretion would reduce cardiovascular events in microalbuminuric subjects (15 to 300 mg/24 hours). Methods and Results— From the Prevention of Renal and Vascular Endstage Disease (PREVEND) cohort (n=8592), 1439 subjects fulfilled the inclusion criteria of the PREVEND Intervention Trial (PREVEND IT). Of these subjects, 864 were randomized to fosinopril 20 mg or matching placebo and to pravastatin 40 mg or matching placebo. The mean follow-up was 46 months, and the primary end point was cardiovascular mortality and hospitalization for cardiovascular morbidity. Mean age was 51±12 years; 65% of subjects were male, and 3.4% had a previous cardiovascular event. Mean cholesterol level was 5.8±1.0 mmol/L, mean systolic/diastolic blood pressure was 130±18/76±10 mm Hg, and median urinary albumin excretion was 22.8 (15.8 to 41.3) mg/24 hours. The primary end point occurred in 45 subjects (5.2%). Fosinopril reduced urinary albumin excretion by 26% ( P <0.001). Subjects treated with fosinopril showed a 40% lower incidence of the primary end point (hazard ratio 0.60 [95% CI 0.33 to 1.10], P =0.098, log-rank). Pravastatin did not reduce urinary albumin excretion, and subjects treated with pravastatin showed a 13% lower incidence of the primary end point than subjects in the placebo group (0.87 [0.49 to 1.57], P =0.649, log-rank). Conclusions— In microalbuminuric subjects, treatment with fosinopril had a significant effect on urinary albumin excretion. In addition, fosinopril treatment was associated with a trend in reducing cardiovascular events. Treatment with pravastatin did not result in a significant reduction in urinary albumin excretion or cardiovascular events.